THE SIGNIFICANCE OF ENTREPRENEURSHIP EDUCATION LITERACY IN THE ERA OF DIGITAL TRANSFORMATION: GRADUATES OF THE POSTPANDEMIC COVID-19 UNEMPLOYMENT CRISIS - Irma Wani Othman; Saifulazry Mokhtar; Adelaine Tham; Kelvin Yong (International Journal of Accounting, Finance and Business, 2021)
In the context of Malaysian higher education institutions and in accordance with the Industrial Revolution 4.0, all corners of the world are predicted to enter the era of mega trends in which digital transformation pervades all aspects of life, necessitating adaptation by the younger generation. This paper discusses the general knowledge and understanding of entrepreneurship education literacy in the digital transformation era. Graduates facing the post-Pandemic Covid-19 unemployment crisis is the study’s primary focus. The qualitative research methodology used is based on the inaugural background, so this paper puts the research lens on a selection of contemporary issues such as emphasis on the university to expose students to have more than one skill through entrepreneurship education, which refers to (i) soft skills as the basis of economic regeneration, (ii) entrepreneurial skills with the existence of new opportunities for entrepreneurs, and (iii) relevance of E-commerce with ICT and technical skills of graduates. Meanwhile, collaboration and industry commitment indicate intense cooperation between higher education institutions, thus providing many benefits to graduates, particularly in overcoming Malaysia’s graduate unemployment crisis. Emphasising the importance of universities and industry working together to increase employment opportunities and graduate marketability, among the issues of concern are (i) involvement of the industry in HEIs, (ii) CEO@Faculty Programme, and (iii) 2u2i Programme and Industrial Training Policy.